Prevalence of malaria disease under the Savar upazila of Dhaka district in Bangladesh (Asian Journal of Medical and Biological Research, 2015)
Malaria is a major public health concern in Bangladesh. The aim of this study was to determine the prevalence of malaria parasites from blood sample. The blood samples were collected from patients of different hospitals at Savar upazila. Malaria prevalence survey was conducted in six malaria endemic areas at Savar upazila of Bangladesh. The microscopic examinations were employed for the diagnosis of malaria infection. The overall prevalence of malaria was found to be 23.48% from 115 blood samples. The highest malaria prevalence was observed at Islamnagar area (30.76%) than other five areas of Savar upazila. According to gender wise distribution, it was observed that male (30.90%) had higher positivity compare to their counterparts (16.67%). As regard to age, the peoples whose ages between 21 to 25 years (88.88%) were mostly suffering from malaria. The seasonal influence of outbreak of this disease was higher in rainy season (37.5%), followed by summer (28%), autumn (16.67%) and spring season (12.5%). Effective control program, accurate information on the incidence and prevalence of malaria is required to minimize and eradicate malaria from Bangladesh.Asian J. Med. Biol. Res. June 2015, 1(1): 53-58